Hepatitis C virus: from molecular virology to antiviral therapy - Bartenschlager, Ralf (Current Topics in Microbiology and Immunology, 2013)
Hepatitis C virus (HCV), a major causative agent of chronic liver disease, is spread throughout the world and around 170 million people are persistently infected. In this volume, world-leading experts in the field of HCV research have compiled the most recent scientific advances to provide a comprehensive and very timely overview of the various facets of HCV. The book starts with a discussion of the possible origin of HCV and its spread among the human population. The focus of the subsequent chapters is on available cell culture and in vivo models before shifting to the molecular and cellular principles underlying the viral replication cycle. These chapters are complemented by insightful descriptions of the innate and adaptive immune responses to HCV as well as the virus-associated pathogenesis. Finally, the development of antiviral therapies, which is closely linked with progress in basic research, and the implementation of those therapies into present and future daily clinical practice are highlighted.